Design of Orthogonal Filtered Multitone Modulation Systems and Comparison among Efficient Realizations. (22nd February 2010) - Moret Moret, Nicola Nicola; Tonello Tonello, Andrea M. Andrea M.
Abstract : We address the efficient realization of a filtered multitone (FMT) modulation system and its orthogonal design. FMT modulation can be viewed as a Discrete Fourier Transform (DFT) modulated filter bank (FB). It generalizes the popular orthogonal frequency division multiplexing (OFDM) scheme by deploying frequency confined subchannel pulses. We compare three realizations that have been described by Cvetković and Vetterli (1998), and Weiss and Stewart (2000), and Tonello (2006). A detailed derivation of them is performed in the time-domain via the exploitation of different FB polyphase decompositions. We then consider the design of an orthogonal FMT system and we exploit the third realization which allows simplifying the orthogonal FB design and obtaining a block diagonal system matrix with independent subblocks. A numerical method is then presented to obtain an orthogonal FB with well frequency confined subchannel pulses for arbitrarily large number of subchannels. Several examples of pulses with minimal length are reported and their performance is evaluated in typical multipath fading channels. Finally, we compare the orthogonal FMT system with a cyclically prefixed OFDM system in the IEEE 802.11 wireless LAN channel. In this scenario, FMT with minimal length pulses and single tap subchannel equalization outperforms the OFDM system in achievable rate.